KERJA SAMA DIREKTORAT JENDERAL BEA CUKAI (DJBC) DENGAN THE GENERAL ADMINISTRATION OF CHINA CUSTOMS (GACC) DALAM UPAYA MENGATASI PENYELUNDUPAN NARKOBA DI INDONESIA - Lukitasari Prima Dewi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
Illegal drug smuggling is an organized transnational crime which needs to be handled since it has a global scope. Indonesia as a sovereign nation has an obligation to protect its national interest to eradicate any drug smuggling activity into Indonesian territory. Indonesia has been doing various efforts, domestically and internationally, to make this goal a reality. In the international aspect, Indonesia is cooperating with China in the customs field. Indonesian Direktorat Jenderal Bea Cukai and General Administration China Customs cooperate in an effort to eradicate numbers of illegal drugs smuggled to Indonesian soil.The purpose of this research is to describe and provide understanding about forms of international cooperation between Direktorat Jenderal Bea Cukai and General Administration China Customs. Research method used in this research is the qualitative method. This research is descriptive and analytical in nature. Concepts utilized in this research are non-traditional security and international cooperation, specifically transgovernmental networks. The results of this research shows that Direktorat Jenderal Bea Cukai and General Administration China Customs have done several efforts in information, knowledge, and assistance with each other to eradicate illegal drug smuggling as an organized transnational crime.